The association of selenium exposure with the odds of metabolic syndrome: a dose-response meta-analysis - Rongrong Yuan; Yu Zhang; Jiakai Han (BMC Endocrine Disorders)
Abstract Background Selenium is a key regulator of metabolic homeostasis. It has been proposed that exposure to selenium might be associated with metabolic syndrome (MetS). However, the results are contradictory. This meta-analysis was carried out to analyze the relationships between selenium levels in biological samples and odds of Mets. Methods We searched Scopus and PubMed databases up until September 2024 to identify relevant studies. Odds ratio (OR) and 95% confidence interval was used to pool the data using a random effects model. Results The meta-analysis encompassed 18 observational studies involving 21,481 participants. It found that higher selenium exposure was related to an elevated likelihood of MetS (OR = 1.30, 95% CI = 1.12–1.51), even after controlling for covariates, such as smoking, age, alcohol consumption, and physical activity. Heterogeneity was significant among the studies (I² = 88.9%, P = 0.001). While elevated serum selenium levels linked to a higher odds of MetS, no such relationship was observed for selenium in urine or toenails. Subgroup analyses indicated that this association was evident only in females (OR = 2.0, 95% CI = 1.17–1.43) and particularly pronounced in individuals aged ≥ 50 years. A dose-response relationship was identified, showing a 6% increase in MetS odds for each additional 10 µg/L of serum selenium, with the odds rising non-linearly when serum levels surpassed 80 µg/L. Conclusions This study suggests that selenium may associated with the odds of MetS, following a dose-response relationship.